The Interpretation of Speech in the Pentateuch Targums: A Study of Method and Presentation in Targumic Exegesis - Samely, Alexander (Texts and Studies in Ancient Judaism, 2020)
Cover -- Titel -- Acknowledgments -- Contents -- Abbreviations -- Introduction -- I. Accounting for the Narrative and the Text -- 1. The Setting of Biblical Speech: Persons, Places, Times -- A. Speakers and Addressees -- Discussion I: Links in the Text -- B. Institutions, Places and Times -- Discussion II: Addition as the Filling of Slots -- 2. The Background of Biblical Speech I: Additional Events and Original Co-Text -- A. Facts and Events in the co-text -- Discussion III: The Relevance of Co-text -- B. Events Integrated as Perception -- Discussion IV: The Targumist as a Story-Teller -- 3. The Background of Biblical Speech II: Added Thoughts and Speech -- Utterance Change -- A. The Behaviour of the Addressee as Background of Requests -- Discussion V: The Increase in Coherence -- B. Speaker Thoughts, Intentions and Errors as Background -- Discussion VI: The Narrative Perspective of the Targumist -- C. Speech as Background Event -- D. Co-ordinated Changes: Additional Events and Modified Utterances -- Discussion VII: Exegesis and Theology in the Targum -- II. Accounting for the Text and the Narrative -- 4. The Cohesion of the Speech Unit: Internal Agreement -- Discussion VIII: The Presentation of Exegesis -- 5. The Coherence of the Pentateuch: Utterances presupposing Utterances -- A. Identifying the Reference of Discourse Deixis -- B. Identifying the Reference of Utterance Mentions -- 1. Modifying the Reference -- Discussion IX: The Completeness of Torah -- 2. Creating the Utterance -- 6. The Relevance of Repetition -- Discussion X: Repetition Inside and Outside Speech Situations -- The Passages in Overview -- III. The Character of Targum -- 7. Targum and the Targums -- A. Targumic Profiles -- B. The Speaker's Perspective in Neofiti -- 8. The Character of Targum -- A. The Question of the Genre of Targum -- B. Some Features of Targumic Exegesis.